1999
DOI: 10.1007/s001340051049
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator delivery by metered-dose inhaler in mechanically ventilated COPD patients: influence of tidal volume

Abstract: We conclude that S delivered with an MDI and a spacer device induces significant bronchodilation in mechanically ventilated patients with COPD, the magnitude of which is not affected by at least a 50% increase in VT. These results do not support the VT manipulations when bronchodilators are administered in adequate doses during controlled mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 19 publications
2
32
0
7
Order By: Relevance
“…It was further shown that the response was evident even when salbutamol was given in relatively low doses and not influenced by the inspiratory flow/time profile during drug delivery. Independent of the dose of salbutamol, DR remained relatively constant throughout the study, indicating that salbutamol acted by dilating the central airways, in line with previous observations [3,13,14]. Although expiratory resistance was not measured in the present study, it was most probably decreased by salbutamol, as indicated by the significant reduction in PEEPi and end-inspiratory static plateau pressure, indirect indices of dynamic hyperinflation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was further shown that the response was evident even when salbutamol was given in relatively low doses and not influenced by the inspiratory flow/time profile during drug delivery. Independent of the dose of salbutamol, DR remained relatively constant throughout the study, indicating that salbutamol acted by dilating the central airways, in line with previous observations [3,13,14]. Although expiratory resistance was not measured in the present study, it was most probably decreased by salbutamol, as indicated by the significant reduction in PEEPi and end-inspiratory static plateau pressure, indirect indices of dynamic hyperinflation.…”
Section: Discussionsupporting
confidence: 91%
“…these recommendations are based mainly on aerosol delivery data [11,12], which may not reflect drug bronchodilator effect. Indeed, in recent studies, it was shown that neither application of a 5 s end-inspiratory pause nor increasing the VT, strategies which probably enhanced drug delivery [4,5,11,12], augmented the bronchodilator effect of six puffs salbutamol [13,14]. The current study demonstrated that, at constant VT and inspiratory time, changing the inspiratory flow/time profile did not have any effect on salbutamol-induced bronchodilation, given via MDI and spacer.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…12,13 This information led to the practice of increasing V T or providing sigh breaths during nebulization. 2 Previous research using a pediatric model of mechanical ventilation with a jet nebulizer, 6 and a clinical study in adults, 14 had opposite findings. We hypothesized that increasing the V T , using a vibrating mesh nebulizer, and placing the nebulizer at the ventilator would increase lung dose and drug delivery efficiency in a pediatric model of mechanical ventilation.…”
Section: Introductionmentioning
confidence: 98%
“…As expected, albuterol decreased the minimum and maximum end-inspiratory R RS ) in mechanically ventilated patients with COPD exacerbation, in agreement with previous studies. 2,4,13 Nonetheless, both with and without albuterol, expiratory resistance at the beginning of expiration was approximately 85% higher than end-inspiratory resistance, and increased more than 3-fold toward the end of expiration. Albuterol-induced decrease in expiratory resistance was greater toward the end of expiration.…”
Section: Discussionmentioning
confidence: 93%